2018
DOI: 10.3390/su10010175
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Sensory Perceptions of Food Consumers towards Technological Innovation in Mexico: A Case-Study on Rice-Based Dessert

Abstract: Innovation in the agro-food system has become a strategy increasingly used by companies as a means to increase their competitiveness and position themselves in the market. In this context, the objective of this work is to identify the attitudes and sensory perceptions of consumers towards food technology through two scales (food technology neophobia and domain specific innovativeness) and hedonic tastings. For this, a new product was selected in the market: powder to prepare rice with milk. Most consumers have… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The attitude toward new food technologies varies according to the population. Studies reported that attitude differs with respect to factors including age, sex, income status, education level, place of residence, food technology neophobia, and environmental attitude (Matin et al ., 2012; Chen et al ., 2013; Jezewska‐Zychowicz & Królak, 2015; De Steur et al ., 2016; Salgado‐Beltrán et al ., 2018; Cattaneo et al ., 2019; Rabadán, 2021; Wendt & Weinrich, 2023). As the approach to new food technologies shapes the food industry and market, defining neophobia in a society is significant.…”
Section: Discussionmentioning
confidence: 99%
“…The attitude toward new food technologies varies according to the population. Studies reported that attitude differs with respect to factors including age, sex, income status, education level, place of residence, food technology neophobia, and environmental attitude (Matin et al ., 2012; Chen et al ., 2013; Jezewska‐Zychowicz & Królak, 2015; De Steur et al ., 2016; Salgado‐Beltrán et al ., 2018; Cattaneo et al ., 2019; Rabadán, 2021; Wendt & Weinrich, 2023). As the approach to new food technologies shapes the food industry and market, defining neophobia in a society is significant.…”
Section: Discussionmentioning
confidence: 99%
“…Polo Otero, Ramos Ruiz, Arrieta Barcasnegras, and González Fernández (2017), while analyzing Colombian food and beverage firms, found that research and development activities favor to a greater extent the realization of product innovation rather than process innovation. Likewise, Salgado-Beltrán, Beltrán-Morales, Velarde-Mendivil, and Robles-Baldenegro, (2018) analyzing the behavior of Mexican food consumers, they found that firms must be very innovative, taking into account that innovative customers are an important part of their market.…”
Section: Introductionmentioning
confidence: 99%
“…El comportamiento del consumidor protagoniza un rol esencial en la relación directa entre el ofertante y el demandante, entiéndase como ofertante aquella persona o institución que pretende satisfacer una necesidad a través de un producto, servicio o incluso idea (Salgado Beltrán et al, 2017); por otro lado, el demandante como aquella persona o institución que carece de algo. Es así, necesario que las empresas, ya sean estas pequeñas, medianas, nacionales e internacionales, conozcan al consumidor (Encarnación, 2019).…”
Section: Introductionunclassified